Drosophila DBT lacking protein kinase activity produces long-period and arrhythmic circadian behavioral and molecular rhythms. - Muskus, M.J.; Preuss, F.; Fan, J.Y.; Bjes, E.S.; Price, J.L. (Molecular and Cellular Biology, 2007)
A mutation (K38R) which specifically eliminates kinase activity was created in the Drosophila melanogaster ckI gene (doubletime [dbt]). In vitro, DBT protein carrying the K38R mutation (DBT(K/R)) interacted with Period protein (PER) but lacked kinase activity. In cell culture and in flies, DBT(K/R) antagonized the phosphorylation and degradation of PER, and it damped the oscillation of PER in vivo. Overexpression of short-period, long-period, or wild-type DBT in flies produced the same circadian periods produced by the corresponding alleles of the endogenous gene. These mutations therefore dictate an altered "set point" for period length that is not altered by overexpression. Overexpression of the DBT(K/R) produced effects proportional to the titration of endogenous DBT, with long circadian periods at lower expression levels and arrhythmicity at higher levels. This first analysis of adult flies with a virtual lack of DBT activity demonstrates that DBT's kinase activity is necessary for normal circadian rhythms and that a general reduction of DBT kinase activity does not produce short periods.